Evaluation of an online training program to improve family routines, parental well-being, and the behavior of children with autism. (October 2018) - Pennefather, Jordan; Hieneman, Meme; Raulston, Tracy J.; Caraway, Nell
Highlights: Combining ABA, ACT, and optimism training approaches may be a viable way to target the needs of parents and children with ASD. Online interventions increase reach and accessibility. Our brief online intervention demonstrated improvements on both parent and child outcomes. Abstract: Background: Parents of children with autism spectrum disorder (ASD) are at an increased risk for stress, and their children often display high rates of problem behavior. There is a robust literature base showing that training parents to implement applied behavior analytic (ABA) interventions helps reduce their child's challenging behavior. However, some parents continue to report high rates of stress that may interfere with implementation. Adding cognitive-affective strategies such as ACT and optimism training to ABA may be beneficial. Telehealth models have the potential to reach parents who may not otherwise be able to access parent training, making evidence-based programs more readily available. Method: Twenty-three parents (with 16 completing posttest assessments) of children with autism (ages four to eight) participated in a three-week online training program. Topics covered included instruction in ABA principles as well as stress reduction strategies and mediation practice based on ACT principles. The intervention included weekly synchronous online meetings with other parents and two parent educators, as well as supplemental assignments completed between sessions. Results: We found that after the intervention parents reported: (1) decreases in parental stress, (2) increases in relevant knowledge, (3) increases in child prosocial behavior, (4) decreases in hyperactive behaviors, and (5) high levels of satisfaction with the intervention. Conclusions: This online program, combining ABA and stress reduction practices, resulted in positive outcomes for children with autism and their families. Although this was a small sample size, this early investigation offers promise for delivering this combined intervention approach effectively online. Training small groups of parents in an online format may be a feasible, efficient service delivery method.